Carrier and developer for electronic photographic imaging, electronic photographic imaging method and device
By adding charged particles A, conductive particles B, dispersant and defoaming agent to the resin layer of the carrier for electrophotography imaging, the problems of increasing resistance of the carrier and decreasing charging capacity are solved, and the effect of inhibiting toner scattering and improving image quality is achieved.
Patent Information
- Application Number
- CN202011244332.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-10
- Filing Date
- 2020-11-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-11-10
AI Technical Summary
In full-color imaging, the increased resistance of the carrier and the reduced charging capacity lead to toner scattering and background pollution, affecting image quality.
A carrier for electrophotographic imaging is adopted, including core particles and a resin layer covering the core particles, the resin layer contains charged particles A and conductive particles B, and a dispersant and defoaming agent are added to the resin layer to control resistance and charging properties.
Effectively control the resistance and charging properties of the carrier, inhibit the dispersion of toner, improve image quality and extend the service life of the carrier.
Smart Images

Figure BDA0002769445760000241 
Figure BDA0002769445760000311 
Figure HDA0002769445770000011
Abstract
Description
Technical Field
[0001] The invention relates to a carrier for electronic photographic imaging, a developer for electronic photographic imaging, an electronic photographic imaging method, an electronic photographic imaging device, and a processing card box. Background Art
[0002] In the imaging of the electrophotographic method, an electrostatic latent image is formed on an electrostatic latent image carrier such as a photoconductive material, and a charged toner is attached to the electrostatic latent image to form a toner image, and then the toner image is transferred to a recording medium, and the transferred image is fixed to become an output image. In recent years, the technology of multi-function machines or printers using the electrophotographic method has rapidly developed from monochrome to full color, and the full color market tends to expand.
[0003] In full-color imaging, three toners of yellow, magenta, and cyan are usually used, or four color toners of black are added, and they are stacked to reproduce all colors. Therefore, in order to obtain a vivid full-color image with excellent color reproducibility, the surface of the toner image after fixing must be smooth to reduce light scattering.
[0004] For the above reasons, in the past, in order to achieve smooth toner images, the electrostatic latent images of full-color copiers and the like mostly achieved high gloss by increasing the amount of toner attached to the electrostatic latent image. Therefore, when printing for a long time, the degraded toner adheres to the surface of the carrier, which becomes a toner consumption (tonerspent) problem. Among the deterioration of the carrier caused by toner consumption, the problems are the increase in the carrier resistance and the decrease in the carrier charging capacity. When the carrier charging capacity decreases, the so-called toner scattering occurs, which contaminates the inside of the machine, thereby causing faults such as sensor misdetection.
[0005] In the mass production printer field, the market has been expanding in recent years, and higher quality images are required than before. In order to achieve high-speed development, the carrier is subjected to strong stress inside the developer, the carrier coating resin is worn, the core material is exposed, and the carrier is transferred to the electrostatic latent image carrier, which is called carrier adhesion. As a result, the color separation occurs at the edge or center of the image, and the demand for this problem has become more urgent in recent years.
[0006] On the other hand, in order to prevent carrier adhesion, the carrier resistance can be designed to a high standard from the initial stage and the resistance can be maintained at a high level. However, in this case, the charge on the surface of the carrier cannot be properly leaked just after development, resulting in undesirable conditions such as fading at the ends when printing halftones.
[0007] Various attempts have been made to solve the above-mentioned disadvantages.
[0008] For example, Patent Document 1 discloses that a carrier contains phosphorus-doped conductive tin oxide particles and has a desired low resistance value. Also, Patent Document 2 discloses a carrier containing barium sulfate in a coating resin, and the Ba / Si ratio relative to all elements measured by XPS is 0.01 to 0.08. The above method has a certain effect in suppressing toner consumption and suppressing film wear of the coating resin layer.
[0009] However, in recent years, in order to reduce power consumption, there is a tendency to fix the toner at low temperatures, and coupled with the demand for faster printing speeds, the toner consumption on the carrier is more likely to occur. Furthermore, due to higher requirements for image quality, the toner tends to contain many additives, resulting in consumption on the carrier. The current situation is that the toner charge is reduced, and the margin for toner scattering and background pollution is reduced. In addition, in order to fix the toner at low temperature, the amount of charged particles is reduced, and the toner and developer are not fully mixed during replenishment, resulting in problems such as no charge and toner scattering. In response to these newly occurring problems, Patent Documents 3 and 4 describe a carrier that contains barium sulfate or magnesium oxide on the outermost surface of the coated resin as particles that impart charging properties.
[0010] [Patent Literature]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 2010-230836
[0012] [Patent Document 2] Japanese Patent Application Publication No. 2011-209678
[0013] [Patent Document 3] Japanese Patent Application Publication No. 2016-212254
[0014] [Patent Document 4] Japanese Patent Application Publication No. 2017-167387 Summary of the invention
[0015] The present invention has been made in view of the above-mentioned background technology, and its object is to provide a carrier for electrophotographic imaging which can control the resistance and charge to a sufficiently low level for the required image quality, and can suppress the adhesion of the carrier and the scattering of the colorant.
[0016] The present inventors have studied to solve the above problems and have found that the above problems can be solved by an electrophotographic image forming support having the following structure (1).
[0017] (1) An electrophotographic imaging carrier, comprising core particles and a resin layer covering the core particles, wherein the resin layer contains charged fine particles A and conductive fine particles B, and contains a dispersant and a defoaming agent.
[0018] The effect of the present invention is described below:
[0019] The carrier for electrophotographic image formation of the present invention can control the resistance and charge to be sufficiently low for the required image quality and can suppress the scattering of toner. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a diagram showing a unit used when measuring the volume resistivity of a carrier.
[0021] Figure 2 It is a figure which shows an example of the process cartridge of this invention. DETAILED DESCRIPTION
[0022] Below, refer to the attached Figure 1 The present invention is not limited to the following embodiments, and other embodiments, additions, corrections, deletions, etc. can be modified by those skilled in the art within the scope of their imagination. Any form of the present invention is also within the scope of the present invention as long as it has the function and effect of the present invention.
[0023] The present invention relates to the following technical solution (1), and also includes the following technical solutions (2) to (12) as embodiments.
[0024] (1) An electrophotographic imaging carrier, comprising core particles and a resin layer covering the core particles, wherein the resin layer contains charged fine particles A and conductive fine particles B, and contains a dispersant and a defoaming agent.
[0025] (2) The carrier for electrophotographic imaging described in (1) above is characterized in that the dispersant is a phosphate-based surfactant.
[0026] (3) The electrophotographic image forming carrier described in (1) or (2) above, wherein the defoaming agent is a silicone-based defoaming agent.
[0027] (4) The carrier for electrophotographic imaging described in any one of (1) to (3) above, characterized in that the charged fine particles A are at least one inorganic fine particle selected from the group consisting of barium sulfate, magnesium oxide, magnesium hydroxide, and hydrotalcite.
[0028] (5) The carrier for electronic photographic imaging described in any one of the above (1) to (4) is characterized in that the conductive particles B are any one of tungsten, indium, and phosphorus, or particles of tin oxide doped with any one of the oxides thereof, or particles in which the doped tin oxide is arranged on the surface of a substrate.
[0029] (6) The electrophotographic image forming carrier described in (5) above is characterized in that the conductive fine particles B are aluminum oxide fine particles in which tin oxide doped with tungsten or an oxide thereof is provided on the surface of the substrate.
[0030] (7) The electrophotographic image forming carrier described in (6) above is characterized in that the charged fine particles A are barium sulfate.
[0031] (8) The carrier for electronic photographic imaging described in any one of (1) to (7) above is characterized in that the amount of the dispersant added is not less than 0.5 parts by mass and not more than 10.0 parts by mass relative to 100 parts by mass of the total amount of the charged fine particles A and the conductive fine particles B.
[0032] (9) The carrier for electrophotographic imaging described in any one of (1) to (8) above, characterized in that the solid content of the defoaming agent added is 0.05 parts by mass or more and 0.35 parts by mass or less relative to 100 parts by mass of the resin layer.
[0033] (10) An electrophotographic imaging carrier, comprising core particles and a resin layer covering the core particles, wherein the resin layer comprises charged particles A and conductive particles B, and contains phosphate ester and silicone oil.
[0034] (11) A developer for electrophotographic image formation, characterized in that the carrier for electrophotographic image formation described in any one of (1) to (10) above is used.
[0035] (12) An electrophotographic imaging method, comprising:
[0036] A process of forming an electrostatic latent image on an electrostatic latent image carrier;
[0037] A step of developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer described in (11) above to form a toner image;
[0038] a step of transferring the toner image formed on the electrostatic latent image carrier to a recording medium; and
[0039] A step of fixing the toner image transferred to the recording medium.
[0040] (13) An electronic photographic imaging device, comprising:
[0041] Electrostatic latent image carrier;
[0042] A charging mechanism for charging the electrostatic latent image carrier;
[0043] an exposure mechanism for forming an electrostatic latent image on the electrostatic latent image carrier;
[0044] A developing device for developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer described in (11) above to form a toner image;
[0045] A transfer mechanism for transferring the toner image formed on the electrostatic latent image carrier to a recording medium; and
[0046] A fixing mechanism fixes the toner image transferred to the recording medium.
[0047] (14) A processing cartridge, characterized in that it comprises:
[0048] Electrostatic latent image carrier;
[0049] A charging component for charging the surface of the electrostatic latent image carrier;
[0050] a developing member for developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer described in (11) above; and
[0051] A cleaning member is provided for cleaning the electrostatic latent image carrier.
[0052] Next, the vector of the present invention is described in detail.
[0053] The carrier for electrophotographic imaging of the present invention comprises core particles and a resin layer covering the core particles, wherein the resin layer contains at least two types of particles, namely, charged particles A and conductive particles B, and contains a dispersant and a defoaming agent.
[0054] In the present invention, it is important that the resin layer contains at least charged particles A and conductive particles B. When the resistance is adjusted to a low resistance range while ensuring sufficient charging capability, it is necessary to introduce two types of particles, charged particles A with high chargeability to the toner and conductive particles B with conductivity. In addition to the conductive particles B, carbon black with excellent resistance adjustment function may be added as one of the conductive particles B. As the amount of carbon black is reduced as it approaches the surface layer, when the resin layer is scratched, the amount of carbon black contained in the coating component that is free from the carrier is reduced, and as a result, color contamination of the toner can be suppressed. In addition, in order to solve the problem of increased resistance near the surface layer due to the reduction in the amount of carbon black, the conductive particles B can be increased the closer to the surface layer where the amount of carbon black is less, so that the surface layer side has the same resistance as the deep layer side where the carbon black concentration is high.
[0055] Furthermore, it is very important that the carrier of the present invention contains a dispersant in the resin layer. In the coating liquid forming the resin layer composed of resin, inorganic particles, diluent solvent, etc., by formulating a dispersant, the inorganic particles can be dispersed to a primary particle size with a narrow particle size distribution. In this way, it is possible to eliminate such coarse particles that are not fully buried in the adhesive resin and are not firmly fixed to the surface of the carrier. The particles are easily detached due to the stress in the initial stage of printing, and the resistance of the carrier is reduced, which leads to the adhesion of the carrier to the solid image part. However, this situation can be suppressed by adding a dispersant.
[0056] In addition, the dispersant has both a group having an affinity for the resin and a group having an affinity for the inorganic particles, and therefore has the effect of improving the affinity between the resin and the inorganic particles. As a result, the adhesion between the resin in the resin layer and the inorganic particles increases, and a more solid film can be formed. Even with the printing stress over time, the particles are difficult to detach from the resin layer. Thus, the adhesion of the carrier to the solid image portion over time can be suppressed. In addition, since the charged particles A that charge the toner can be suppressed from detaching, the charging ability of the toner can be maintained even over a long period of time, and the toner is difficult to scatter.
[0057] At this time, it is very important to add a defoamer in addition to the dispersant. When a dispersant is added to the coating liquid that forms the coating layer composed of resin, inorganic particles, diluent solvent, etc., the coating liquid is easy to foam because the dispersant is a so-called surfactant. When the foaming coating liquid is used for coating, a resin layer is formed in a state where bubbles are taken in, and the holes caused by the taken-in bubbles will form cavities in the resin layer. The cavities in the resin layer significantly reduce the durability of the film, and as the printing time passes, the film scratches gradually become more serious. Therefore, only adding a dispersant cannot fully obtain the effect of inhibiting the adhesion of the carrier to the solid image part of the above-mentioned printing for a long time and the effect of preventing the colorant from scattering. However, by adding a defoamer in addition to the dispersant, the foaming of the coating liquid can be suppressed, and the cavities in the resin layer can be eliminated. As a result, the problem of reduced durability of the film after printing for a long time is solved, and not only in the initial stage of printing, but also even after printing for a long time, a carrier that inhibits the adhesion of the carrier to the solid image part and the scattering of the colorant can be obtained.
[0058] There are no particular restrictions on the dispersant, and examples thereof include phosphate surfactants, sulfate surfactants, sulfonic acid surfactants, and carboxylic acid surfactants. Among them, phosphate surfactants are preferred. By using a dispersant, the charged particles A and the conductive particles B can be well dispersed until the primary particle size, so that the distribution of the inorganic particles in the resin layer is homogenized, and the affinity between the resin and the inorganic particles can be improved. In addition, according to the research results of the inventors, it was found that by adding a dispersant having a phosphate structure, the margin for preventing the colorant from scattering can be further improved. This is because the structural part of the phosphate ester is positively charged relative to the negatively charged colorant. When a dispersant containing a phosphate ester is added, the chargeability with the colorant is improved compared to the case when it is not added. In particular, the chargeability just after mixing and stirring with the colorant, that is, the so-called initial chargeability is good, and therefore, it has a good effect on suppressing the colorant from being fully charged during replenishment, resulting in the scattering of the colorant.
[0059] The phosphate ester surfactant as the dispersant preferably contains phosphate ester as the main component. In the present embodiment, in order to be the "main component", the dispersant preferably contains 50% by mass or more of phosphate ester, more preferably 90% by mass or more.
[0060] Commercially available products include, but are not limited to, SOLSPERSE 2000, 2400, 2600, 2700, and 2800 (manufactured by ZENECA), AJISPER PB711, PA111, PB811, and PW911 (manufactured by Ajinomoto Co., Ltd.), EFKA-46, 47, 48, and 49 (manufactured by EFKA Chemical Co., Ltd.), DISPERBIC 160, 162, 163, 166, 170, 180, 182, 184, and 190 (manufactured by BYK), and FLOREN DOPA-158, 22, 17, G-700, TG-720W, and 730W (manufactured by Kyoeisha Chemical Co., Ltd.).
[0061] The amount of dispersant added is preferably 0.5 parts by mass or more and 10.0 parts by mass or less relative to the total amount of 100 parts by mass of the charged particles A and the conductive particles B. When the amount of dispersant added is less than 0.5 parts by mass, the inorganic particles cannot be fully dispersed until the primary particle size, and inorganic particles in a coagulated state remain. Such coagulated particles are not fully fixed to the resin layer, and the stress in the initial stage of printing causes detachment, which reduces the resistance and causes the carrier to adhere. In addition, the amount of dispersant present on the outermost surface of the resin layer is small, and good initial chargeability is not shown, and the superiority of toner scattering cannot be obtained.
[0062] When the amount of dispersant added exceeds 10.0 parts by mass, a large amount of dispersant components that cannot be adsorbed on inorganic particles exist in the coating resin. As a result, the proportion of the binder resin in the resin layer is reduced, the durability of the film is reduced, the inorganic particles are separated after a long period of printing, and the carrier adheres to the solid image part or the toner is scattered after a long period of printing. Therefore, relative to the total amount of 100 parts by mass of the charged particles A and the conductive particles B, it is preferably contained in an amount of 0.5 parts by mass or more and 10.0 parts by mass or less, and more preferably 1.0 parts by mass or more and 3.0 parts by mass or less.
[0063] There are no particular restrictions on the defoaming agent, and examples thereof include silicone, acrylic, and vinyl. Among them, silicone is preferred. In order to exert the defoaming effect, the balance of compatibility and incompatibility with the solvent is important. Silicones have a good balance of compatibility and incompatibility, and even a small amount of addition can obtain a good defoaming effect, which can inhibit the generation of voids in the coating resin. As the silicone defoaming agent, silicone oil is preferably used.
[0064] Commercially available products include KS-530, KF-96, KS-7708, KS-66, KS-69 (manufactured by Shin-Etsu Silicone Co., Ltd.), TSF451, THF450, TSA720, YSA02, TSA750, TSA750S (manufactured by MOMENYIVE PERFORMANCE MATERIALS Co., Ltd.), BYK065, BYK-066N, BYK070, BYK-088, BYK-141 (manufactured by BYK Co., Ltd.), DISPARON 1930N, DISPARON 1933, DISPARON 1934 (manufactured by Kusumoto Chemicals Co., Ltd.), etc., but are not limited to these.
[0065] The solid content (solid content) of the defoaming agent added is preferably 0.05 parts by mass or more and 0.35 parts by mass or less relative to 100 parts by mass of the resin layer.
[0066] When the solid content of the defoamer is less than 0.05 parts by mass, the defoaming effect cannot be fully obtained, and voids are generated in the coating resin. When the amount of the defoamer added exceeds 0.35 parts by mass, a surface defect of the coating film called a depression appears, the resin layer on the surface of the carrier becomes brittle, the inorganic particles are easily detached, and the carrier adheres to the solid image part worsens. Regarding the amount of the defoamer added relative to the coating liquid, when the solid content concentration of the defoamer is set to 1%, the amount of the defoamer added relative to the total amount of 100 parts by mass of the coating liquid is preferably 1.0 parts by mass or more and 10.0 parts by mass or less. More preferably, it is 3.0 parts by mass or more and 7.0 parts by mass or less.
[0067] In addition, the charged particles A are preferably inorganic particles selected from barium sulfate, magnesium oxide, magnesium hydroxide, and hydrotalcite. When using a negatively charged toner, by selecting the above-mentioned material having positive chargeability, the long-term charging ability can be stabilized. In particular, barium sulfate has a high charging ability for negatively charged toners, is white, and has little effect on the color tone of the toner even when it is separated from the coating resin, and has good usability.
[0068] The charged particles A preferably have an equivalent circular diameter of 400 nm or more and 900 nm or less. If within this range, the charged particles A can be present in a convex state relative to the carrier coating surface, and the chargeability with the toner can be ensured. In order to ensure stable charging ability and developing ability, the equivalent circular diameter of the charged particles A is more preferably 600 nm or more. In addition, if the equivalent circular diameter of the charged particles A is 900 nm or less, the particle size of the charged particles A will not be too large relative to the thickness of the coating film, and therefore, it is fully maintained in the binding resin and is difficult to detach from the coating resin film, and therefore, it is very suitable.
[0069] As long as the powder resistivity of the conductive particles B is less than 200Ω·cm, existing materials and new materials can be used. By adding charged particles A and dispersants to the formula, the durability of the film is improved, and the surface of the resin layer containing the conductive particles B is suppressed to a small extent. However, even so, abrasion will still occur due to long-term small amounts of scratches. At this time, in order to minimize the color contamination of the toner caused by the conductive particles B detached from the resin layer or the conductive particles B contained in the detached resin layer, it is preferred that the conductive particles B are as white or as close to colorless as possible.
[0070] As materials with good color and conductive function, compounds in which tungsten, indium, phosphorus or any of their oxides are doped into tin oxide can be cited. The tin oxide can be used as a single substance or as fine particles in which the compound is provided on the surface of a base particle. As the base particle, conventional materials or new materials can be used, and examples thereof include aluminum oxide and titanium oxide.
[0071] In addition, the equivalent circle diameter of the conductive particles B is preferably 600 nm or more and 1000 nm or less. If it is 600 nm or more, the particle size will not be too small, and the carrier resistance can be effectively reduced. If it is 1000 nm or less, it is difficult to separate from the surface of the resin layer. If the conductive particles B that play the function of adjusting resistance are difficult to separate, the carrier resistance is difficult to change, and the image quality stability is improved.
[0072] As the coating resin of the carrier, silicone resin, acrylic resin, or a combination thereof can be used. Acrylic resin has strong adhesion and low brittleness, and therefore has very excellent wear resistance, but has high surface energy. Therefore, when combined with consumable toner, sometimes it produces undesirable conditions such as reduced charge amount due to the accumulation of toner component consumption. On the other hand, silicone resin has low surface energy, and therefore, the toner component is difficult to consume, and the effect of consuming components that cause film wear is difficult to accumulate can be obtained. Therefore, as a coating resin for the carrier, this problem can be solved by using silicone resin in combination. However, silicone resin has weak adhesion and high brittleness, and therefore has the weakness of poor wear resistance. Therefore, it is important to balance the properties of these two resins well, thereby obtaining a coating film that is not easy to consume and has wear resistance, and the improvement effect is significant. This is because the surface energy of silicone resin is low, so that the toner component is difficult to consume, and the effect of consuming components that cause film wear is difficult to accumulate can be obtained.
[0073] The silicone resin described in this specification refers to all commonly known silicone resins, and examples thereof include, but are not limited to, straight-chain silicones consisting only of organic siloxane bonds, silicone resins modified with alkyd, polyester, epoxy resin, acrylic acid, urethane, etc. For example, commercially available straight-chain silicone resins include KR271, KR255, KR152 manufactured by Shin-Etsu Chemical Co., Ltd., SR2400, SR2406, SR2410 manufactured by Toray Dow Corning Silicon Co., Ltd., etc. In this case, the silicone resin monomer may be used alone, or other components for cross-linking reaction, components for adjusting charge, etc. may be used simultaneously. Examples of modified silicone resins include KR206 (alkyd modified), KR5208 (acrylic modified), ES1001N (epoxy modified), and KR305 (urethane modified) manufactured by Shin-Etsu Chemical Co., Ltd., and SR2115 (epoxy modified) and SR2110 (alkyd modified) manufactured by Toray Dow Corning Silicon Co., Ltd.
[0074] The acrylic resin described in this specification refers to all resins having acrylic components, without particular limitation. An acrylic resin monomer may be used, and at least one other component that undergoes a cross-linking reaction may also be used simultaneously. The other components that undergo a cross-linking reaction described herein may include, for example, amino resins, acidic catalysts, etc., but are not limited thereto. The amino resin described herein refers to guanamine, melamine resin, etc., but are not limited thereto. The acidic catalyst described herein may use all acidic catalysts that have a catalytic effect. For example, an acidic catalyst having a reactive group of a fully alkylated type, a hydroxymethyl type, an imino type, a hydroxymethyl / imino type, etc., but are not limited thereto.
[0075] The volume average particle size of the carrier of the present invention is preferably 28 μm or more and 40 μm or less. If the volume average particle size of the carrier particles is 28 μm or more, carrier adhesion will not occur, and if it is 40 μm or less, the reproducibility of image details will not be reduced, and fine images will not be unable to be formed.
[0076] The volume average particle size can be measured using, for example, Microtrac particle size distribution analyzer Model HRA9320-X100 (manufactured by Nikkiso Co., Ltd.).
[0077] The volume resistivity of the carrier of the present invention is preferably 8 to 16 (LogΩ·cm). When the volume resistivity is 8 (LogΩ·cm) or more, carrier adhesion does not occur in non-image areas, and when it is 16 (LogΩ·cm) or less, edge effects do not reach an unacceptable level.
[0078] Volume resistivity can be used Figure 1 The unit shown is measured. Specifically, first, an electrode 1a and an electrode 1b with a surface area of 2.5 cm × 4 cm are separated by a distance of 0.2 cm and stored in a fluororesin container 2, and a carrier 3 is filled in the unit formed by the container 2, and the unit is knocked 10 times at a drop height of 1 cm and a knocking speed of 30 times / minute. Then, a DC voltage of 1000 V is applied between the electrodes 1a and 1b, and the resistance value r [Ω] after 30 seconds is measured using a high resistance meter 4329A (manufactured by Yokogawa Electric Corporation). The volume resistivity [Ω·cm] can be calculated according to the following formula 1.
[0079] r×(2.5×4) / 0.2 (Formula 1)
[0080] As the coating resin, a silicone resin, an acrylic resin, or a combination thereof can be used. In this case, the film strength can be improved by crosslinking by polycondensing the silanol groups under the action of a polycondensation catalyst.
[0081] As polycondensation catalysts, titanium catalysts, tin catalysts, zirconium catalysts, and aluminum catalysts can be cited. In the present invention, among the various catalysts mentioned above, among the titanium catalysts that bring excellent results, diisopropyl di(acetylacetonato)titanate is particularly preferred as a catalyst. It is believed that this is because the effect of promoting the condensation reaction of silanol groups is good and the catalyst is not easily deactivated.
[0082] In the present invention, the resin layer composition preferably contains a silane coupling agent so that the fine particles can be dispersed stably.
[0083] The silane coupling agent is not particularly limited, and examples thereof include r-(2-aminoethyl)aminopropyltrimethoxysilane, r-(2-aminoethyl)aminopropylmethyldimethoxysilane, r-methacryloxypropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-r-aminopropyltrimethoxysilane hydrochloride, r-ethoxypropyltrimethoxysilane, r-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltriacetoxysilane, r-chloropropyltrimethoxysilane, hexamethyldisilazane, r-phenylene glycol, and r-ethoxypropyltrimethoxysilane. Aminopropyltrimethoxysilane, vinyltrimethoxysilane, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, r-chloropropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, allyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, dimethyldiethoxysilane, 1,3-divinyltetramethyldisilazane, methacryloxyethyldimethyl(3-trimethoxysilylpropyl)ammonium chloride, and the like may be used in combination of two or more.
[0084] Examples of commercially available silane coupling agents include AY43-059, SR6020, SZ6023, SH6026, SZ6032, SZ6050, AY43-310M, SZ6030, SH6040, AY43-026, AY43-031, SH6062, Z-6911, SZ6300, SZ6075, SZ6079, SZ6083, SZ6070, SZ6072, Z-6721, and AY43-00 4. Z-6187, AY43-021, AY43-043, AY43-040, AY43-047, Z-6265, AY43-204M, AY43-048, Z-6403, AY43-206M, AY43-206E, Z6341, AY43-210MC, AY43-083, AY43-101, AY43-013, AY43-158E, Z-6920, Z-6940 (manufactured by Toray Silicon Co., Ltd.), etc.
[0085] The amount of the silane coupling agent added is preferably 0.1 to 10% by mass relative to the silicone resin. If the amount of the silane coupling agent added is 0.1% by mass or more, the adhesion between the core particles, the conductive particles and the silicone resin will not be reduced, and the resin layer will not fall off during long-term use. In addition, if it is 10% by mass or less, toner filming will not occur during long-term use.
[0086] In the present invention, the core particles are not particularly limited as long as they are magnetic, and include ferromagnetic metals such as iron and cobalt, iron oxides such as magnetite, hematite, and ferrite, various alloys and compounds, and resin particles in which the above magnetic materials are dispersed in resin, etc. Among them, Mn-based ferrites, Mn-Mg-based ferrites, Mn-Mg-Sr ferrites, etc. are preferred in consideration of the environment.
[0087] There is no particular restriction on the volume average particle size of the core material of the carrier used in the present invention. However, from the viewpoint of preventing carrier adhesion and carrier scattering, the volume average particle size is preferably greater than 20 μm. From the viewpoint of preventing abnormal images such as carrier streaks and preventing image quality degradation, it is preferably less than 100 μm, and more preferably 28 to 40 μm, which can more appropriately respond to the recent high image quality.
[0088] The average film thickness of the resin layer is preferably 0.50 μm or more. When the average film thickness is 0.50 μm or more, a coating film having no film defects and capable of sufficiently retaining fine particles can be formed.
[0089] The developer for electrophotographic image formation of the present invention contains the carrier of the present invention.
[0090] The two-component developer of the present invention contains the carrier of the present invention and a toner. The toner is preferably a negatively charged toner.
[0091] The toner contains a binder resin and a colorant, and can be either a monochrome toner or a color toner. Furthermore, in order to be suitable for an oil-free system in which no oil is applied to the fixing roller to prevent the toner from solidifying, the toner particles may also contain a release agent. Such a toner is usually prone to film formation, but the carrier of the present invention can suppress film formation, and therefore, the developer of the present invention can maintain good quality for a long time. Furthermore, color toners, especially yellow toners, usually cause color contamination due to the wear of the resin layer of the carrier, but the developer of the present invention can suppress the occurrence of color contamination.
[0092] Toner can be produced by a known method such as a pulverization method or a polymerization method. For example, when a toner is produced by a pulverization method, first, the toner material is kneaded to obtain a molten kneaded product, which is then cooled, pulverized, and classified to prepare a master batch. Next, in order to further improve transferability and durability, an external additive is added to the master batch to prepare a toner.
[0093] At this time, there is no particular limitation on the device for mixing the colorant material, and examples thereof include an intermittent two-roll mill, a Banbury mixer, a continuous twin-screw extruder such as a KTK twin-screw extruder (manufactured by Kobe Steel), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a Magic KCK (manufactured by Asada Iron Works Co., Ltd.), a PCM twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd.), and a KEX twin-screw extruder (manufactured by Kurimoto Iron Works Co., Ltd.), and a continuous single-screw mixer such as a CO-KNEADER (manufactured by Buss Co., Ltd.).
[0094] When the cooled melt-kneaded product is pulverized, it can be roughly pulverized using a hammer mill, a rotary compound mill, etc., and then finely pulverized using a jet air flow fine pulverizer, a mechanical fine pulverizer, etc. It is preferably pulverized to an average particle size of 3 to 15 μm.
[0095] When the pulverized melt-kneaded product is classified, a wind-type classifier or the like may be used, and the classification is preferably performed so that the average particle size of the mother particles is 5 to 20 μm.
[0096] Furthermore, when adding an external additive to the masterbatch, the external additive may be mixed and stirred using a mixer, and the external additive may be crushed and attached to the surface of the masterbatch.
[0097] The binder resin is not particularly limited, and examples thereof include single polymers of styrene and its substitutes such as polystyrene, polyparastyrene, and polyethylene-toluene; styrene-based copolymers such as styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-methacrylic acid copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, and styrene-maleate copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polyester, polyurethane, epoxy resin, polyvinyl butyral, polyacrylic acid, rosin, modified rosin, terpene resins, phenolic resins, aliphatic or aromatic hydrocarbon resins, aromatic petroleum resins, and the like; and two or more thereof may be used in combination.
[0098] There are no particular restrictions on the binder resin used for pressure fixing, and examples include polyolefins such as low molecular weight polyethylene and low molecular weight polypropylene, olefin copolymers such as ethylene-acrylic acid copolymers, ethylene-acrylate copolymers, styrene-methacrylic acid copolymers, ethylene-methacrylate copolymers, ethylene-vinyl chloride copolymers, ethylene-vinyl acetate copolymers, and ionomer resins, epoxy resins, polyesters, styrene-butadiene copolymers, polyvinyl pyrrolidone, methyl vinyl ether-anhydrous maleic acid copolymers, maleic acid-modified phenolic resins, phenol-modified terpene resins, etc., and two or more thereof may be used in combination.
[0099] As coloring agents (pigments or dyes), there are no particular restrictions, and examples include yellow pigments such as cadmium yellow, mineral fast yellow, nickel titanium yellow, Nabur yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and lemon yellow lake; orange pigments such as molybdenum orange, permanent orange GTR, pyrazolone orange, Vulcan orange, indanthrene brilliant orange RK, benzidine orange G, and indanthrene brilliant orange GK; red lead, cadmium red, permanent red 4R, lithosol red, pyrazolone red, red calcium salt, lake red D, brilliant red carmine 6B, azure lake, and rhodan Red colors such as Bright Lake B, Alizarin Red Lake, and Brilliant Carmine 3B; purple pigments such as Fast Violet B and Methyl Violet; blue pigments such as Cobalt Blue, Alkali Blue, Victoria Blue Lake, Phthalocyanine Blue, Metal-free Phthalocyanine Blue, Partially Chlorinated Phthalocyanine Blue, Fast Sky Blue, and Indanthrene Blue BC; green pigments such as Chrome Green, Chromium Oxide, Pigment Green B, and Malachite Green Lake; azine pigments such as carbon black, oil furnace black, channel black, lamp black, acetylene black, and aniline black, black pigments such as metal salt azo pigments, metal oxides, and composite metal oxides, etc., and the like can be used in combination of two or more.
[0100] The release agent is not particularly limited, and examples thereof include polyolefins such as polyethylene and polypropylene, fatty acid metal salts, fatty acid esters, paraffin wax, amide wax, polyol wax, silicone oil varnish, carnauba wax, ester wax, and the like, and two or more thereof may be used in combination.
[0101] The toner may further contain a charge control agent. The charge control agent is not particularly limited, and examples thereof include aniline black; azine dyes containing an alkyl group having 2 to 16 carbon atoms; CIBasic Yello 2 (CI41000), CIBasic Yello 3, CIBasic Red 1 (CI45160), CIBasic Red 9 (CI42500), CIBasic Violet 1 (CI42535), CIBasic Violet 3 (CI42555), CIBasic Violet 10 (CI45170), CIBasic Violet 14 (CI42510), CIBasic Blue 1 (CI42025), CIBasic Blue 3 (CI51005), CIBasic Blue 5 (CI42140), CIBasic Blue 7 (CI42595), CIBasic Blue 9 (CI52015), CIBasic Blue Basic dyes such as CIBasic Blue 24 (CI52030), CIBasic Blue 25 (CI52025), CIBasic Blue 26 (CI44045), CIBasic Green 1 (CI42040), CIBasic Green 4 (CI42000), etc.; lake pigments of these basic dyes; quaternary ammonium salts such as CISolvent Black 8 (CI26150), benzoylmethylhexadecyl ammonium chloride, decyltrimethyl chloride, etc.; dialkyltin compounds such as dibutyl and dioctyl; dialkyltin borate compounds; guanidine derivatives; polyamine resins such as vinyl polymers with amino groups and condensation polymers with amino groups; metal complex salts of monoazo dyes; salicylic acid; metal complexes of dialkylsalicylic acid, naphthoic acid, and dicarboxylic acids such as Zn, Al, Co, Cr, FE, etc.; sulfonated copper phthalocyanine pigments; organic boron salts; fluorine-containing quaternary ammonium salts; calixarene compounds, etc., and two or more thereof can be used in combination. Among color toners other than black, white metal salts of salicylic acid derivatives and the like are preferred.
[0102] As external additives, there are no particular restrictions, and inorganic particles such as silicon dioxide, titanium oxide, aluminum oxide, silicon carbide, silicon nitride, and boron nitride can be listed; resin particles such as polymethyl methacrylate particles and polystyrene particles with an average particle size of 0.05 to 1 μm obtained by soap-free emulsion polymerization, etc., can be used in combination of two or more. Among them, metal oxide particles such as silicon dioxide and titanium oxide with hydrophobic surfaces are preferred. In addition, with hydrophobic silicon dioxide and hydrophobic titanium oxide, relative to hydrophobic silicon dioxide, the amount of hydrophobic titanium oxide added is large, and a toner with excellent charge stability to humidity can be obtained.
[0103] By applying the carrier of the present invention to an imaging device, in which a replenishing developer is composed of a carrier and a colorant, and an image is formed while the remaining developer in the developing device is discharged, a stable image quality can be obtained over a very long period of time. That is, the degraded carrier in the developing device is replaced with a non-degraded carrier in the replenishing developer, and the charge is stably maintained for a long period of time, thereby obtaining a stable image. This method is particularly effective when printing a larger image area. When printing a larger image area, the main carrier degradation is the charge deterioration of the carrier due to the consumption of the colorant by the carrier. However, by using the method of the present invention, when the printed image area is large, the replenishment amount of the carrier is also increased, and therefore, the frequency of replacing the degraded carrier is also increased. As a result, a stable image can be obtained over a very long period of time.
[0104] The mixing ratio of the supplementary developer is preferably set to a mixing ratio of more than 2 parts by mass and less than 50 parts by mass of the toner relative to 1 part by mass of the carrier. When the toner is more than 2 parts by mass, since the carrier supply will not be excessive, the carrier concentration in the developing device will not be too high, and therefore, the charge amount of the developer is difficult to increase. An increase in the charge amount of the developer will lead to a decrease in the developing ability and a decrease in the image density. In addition, if the toner is less than 50 parts by mass relative to 1 part by mass of the carrier, the proportion of the carrier in the supplementary developer will not be reduced, and therefore, the replacement of the carrier in the imaging device will increase, and the effect of suppressing the deterioration of the carrier can be expected.
[0105] As the two-component developer, the toner concentration in the developer is preferably in the range of 4% by mass or more and 9% by mass or less. When it is 4% by mass or more, the toner amount is large and a suitable image density can be obtained. When it is 9% by mass or less, the toner of the carrier is easy to maintain and it is difficult to cause the toner to scatter.
[0106] (Imaging Method)
[0107] The imaging method of the present invention comprises:
[0108] A process of forming an electrostatic latent image on an electrostatic latent image carrier;
[0109] A step of developing the electrostatic latent image formed on the electrostatic latent image carrier using the two-component developer of the present invention to form a toner image;
[0110] a step of transferring the toner image formed on the electrostatic latent image carrier to a recording medium; and
[0111] A process of fixing the toner image transferred to the recording medium.
[0112] (Processing Cartridge)
[0113] The processing cartridge of the present invention comprises:
[0114] Electrostatic latent image carrier;
[0115] A charging component for charging the surface of the electrostatic latent image carrier;
[0116] A developing member for developing the electrostatic latent image formed on the electrostatic latent image carrier using the two-component developer of the present invention; and
[0117] A cleaning member is provided for cleaning the electrostatic latent image carrier.
[0118] Figure 2 An example of a process cartridge of the present invention is shown. The process cartridge 10 integrally supports a photosensitive body 11 as an electrostatic latent image carrier, a charging device 12 as a charging component for charging the photosensitive body 11, a developing device 13 as a developing component for developing the electrostatic latent image formed on the photosensitive body 11 using the developer of the present invention to form a toner image, and a cleaning device 14 as a cleaning member for removing the toner remaining on the photosensitive body 11 after the toner image formed on the photosensitive body 11 is transferred to a recording medium. The process cartridge 10 can be attached to and detached from the main body of an imaging device such as a copier or a printer.
[0119] The following is a method for forming an image using an image forming apparatus equipped with a process cartridge 10. First, the photoreceptor 11 is driven to rotate at a predetermined circumferential speed, and the circumferential surface of the photoreceptor 11 is uniformly charged with a predetermined positive or negative potential by the charging device 12. Next, exposure light is irradiated to the circumferential surface of the photoreceptor 11 from an exposure device such as an exposure device of a slit exposure method or an exposure device of a laser scanning exposure method, and an electrostatic latent image is sequentially formed. Furthermore, the electrostatic latent image formed on the circumferential surface of the photoreceptor 11 is developed using the developer of the present invention by the developing device 13 to form a toner image. Next, the toner image formed on the circumferential surface of the photoreceptor 11 is sequentially transferred to a transfer paper that is supplied from a paper supply unit (not shown) between the photoreceptor 11 and the transfer device in synchronization with the rotation of the photoreceptor 11. Furthermore, the transfer paper to which the toner image is transferred is separated from the circumferential surface of the photoreceptor 11, introduced into a fixing device for fixing, and then discharged as a copy (COPY) to the outside of the image forming apparatus. On the other hand, the surface of the photoreceptor 11 after the toner image is transferred is cleaned by removing the residual toner by the cleaning device 14, and then is de-charged by the de-charge device, and is repeatedly used for image formation.
[0120] (Imaging device)
[0121] The imaging device of the present invention comprises:
[0122] Electrostatic latent image carrier;
[0123] A charging mechanism for charging the electrostatic latent image carrier;
[0124] an exposure mechanism for forming an electrostatic latent image on the electrostatic latent image carrier;
[0125] A developing mechanism for developing the electrostatic latent image formed on the electrostatic latent image carrier using a developer to form a toner image;
[0126] A transfer mechanism for transferring the toner image formed on the electrostatic latent image carrier to a recording medium; and
[0127] A fixing mechanism fixes the toner image transferred to the recording medium.
[0128] The imaging device of the present invention may further include other means (mechanisms) appropriately selected as needed, such as de-electrification means, cleaning means, recycling means, control means, etc., and use the two-component developer of the present invention as the developer.
[0129] [Example]
[0130] Hereinafter, the present invention will be described in more detail by giving examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, in the following description, "parts" means "parts by mass" and "%" means "% by mass".
[0131] (Example 1)
[0132] <Resin liquid 1>
[0133] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0134] Silicone resin solution (solid content: 40%) 2000 parts
[0135] ·Aminosilane (solid content: 100%) 35 parts
[0136] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0137] (Powder resistivity: 40[Ω·cm])
[0138] ·Barium sulfate 680 parts
[0139] (Average particle size: 0.60 [μm])
[0140] ·Toluene 6000 parts
[0141] Dispersant (phosphate surfactant) 37 parts
[0142] Defoaming agent (silicone, solid content concentration: 1%) 550 parts
[0143] In the resin liquid 1, each of the above materials is dispersed by a homogenizer for 10 minutes to prepare a resin layer forming liquid. Cu-Zn ferrite with a volume average particle size of 35 μm is used as the carrier core material. The resin liquid 1 is applied to the surface of the core material at a ratio of 30 g / min at 60°C by Spiracoater SP-40 (manufactured by Okada Seiko Co., Ltd.) to a thickness of 0.50 μm, and then dried. The obtained carrier is fired at 230°C in an electric furnace for 1 hour. After cooling, it is crushed using a sieve with a mesh of 100 μm to obtain carrier 1. The average thickness T from the surface of the core material to the surface of the resin layer is 0.50 μm.
[0144] The volume average particle size of the core material was measured using an SRA-type Microtrac particle size analyzer (manufactured by Nikkiso Co., Ltd.) and was set within a range of 0.7 μm to 125 μm.
[0145] The thickness T (μm) from the core material surface to the resin layer surface was measured using a transmission electron microscope (TEM) to observe the cross section of the carrier. The thickness T from the core material surface to the resin layer surface was measured at 50 points along the carrier surface at intervals of 0.2 μm, and the measured values were averaged.
[0146] (Example 2)
[0147] Except that the phosphate surfactant was changed to a sulfate surfactant, the other steps were the same as in Example 1 to obtain a carrier 2.
[0148] (Example 3)
[0149] Except that the phosphate surfactant was changed to a sulfonic acid surfactant, the other steps were the same as in Example 1 to obtain a carrier 3.
[0150] (Example 4)
[0151] Except that the phosphate surfactant was changed to a carboxylic acid surfactant, the other steps were the same as in Example 1 to obtain a carrier 4.
[0152] (Example 5)
[0153] Except that the silicone defoaming agent was changed to an acrylic defoaming agent, the other steps were the same as those in Example 1 to obtain a carrier 5.
[0154] (Example 6)
[0155] Except that the silicone defoaming agent was changed to a vinyl defoaming agent, the other steps were the same as in Example 1 to obtain a carrier 6.
[0156] (Example 7)
[0157] <Resin liquid 7>
[0158] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0159] Silicone resin solution (solid content: 40%) 2000 parts
[0160] ·Aminosilane (solid content: 100%) 35 parts
[0161] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0162] (Powder resistivity: 40[Ω·cm])
[0163] ·Barium sulfate 680 parts
[0164] (Average particle size: 0.60 [μm])
[0165] ·Toluene 6000 parts
[0166] Dispersant (phosphate surfactant) 10 parts
[0167] Defoaming agent (silicone, solid content concentration: 1%) 550 parts
[0168] Except that the resin liquid 1 was changed to the resin liquid 7, the other procedures were the same as those in Example 1 to obtain the carrier 7.
[0169] (Example 8)
[0170] <Resin liquid 8>
[0171] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0172] Silicone resin solution (solid content: 40%) 2000 parts
[0173] ·Aminosilane (solid content: 100%) 35 parts
[0174] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0175] (Powder resistivity: 40[Ω·cm])
[0176] ·Barium sulfate 680 parts
[0177] (Average particle size: 0.60 [μm])
[0178] ·Toluene 6000 parts
[0179] Dispersant (phosphate surfactant) 180 parts
[0180] Defoaming agent (silicone, solid content concentration: 1%) 550 parts
[0181] Except that the resin liquid 1 was changed to the resin liquid 8, the other procedures were the same as those in Example 1 to obtain the carrier 8.
[0182] (Example 9)
[0183] <Resin liquid 9>
[0184] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0185] Silicone resin solution (solid content: 40%) 2000 parts
[0186] ·Aminosilane (solid content: 100%) 35 parts
[0187] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0188] (Powder resistivity: 40[Ω·cm])
[0189] ·Barium sulfate 680 parts
[0190] (Average particle size: 0.60 [μm])
[0191] ·Toluene 6000 parts
[0192] Dispersant (phosphate surfactant) 37 parts
[0193] · Defoaming agent (silicone, solid content concentration: 1%) 160 parts
[0194] Except that the resin liquid 1 was changed to the resin liquid 9, the other procedures were the same as those in Example 1 to obtain the carrier 9.
[0195] (Example 10)
[0196] <Resin liquid 10>
[0197] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0198] Silicone resin solution (solid content: 40%) 2000 parts
[0199] ·Aminosilane (solid content: 100%) 35 parts
[0200] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0201] (Powder resistivity: 40[Ω·cm])
[0202] ·Barium sulfate 680 parts
[0203] (Average particle size: 0.60 [μm])
[0204] ·Toluene 6000 parts
[0205] Dispersant (phosphate surfactant) 37 parts
[0206] · Defoamer (silicone, solid content concentration: 1%) 940 parts
[0207] Except that the resin liquid 1 was changed to the resin liquid 10 , the other steps were the same as those in Example 1 to obtain the carrier 10 .
[0208] (11 cases implemented)
[0209] <Resin liquid 11>
[0210] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0211] Silicone resin solution (solid content: 40%) 2000 parts
[0212] ·Aminosilane (solid content: 100%) 35 parts
[0213] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0214] (Powder resistivity: 40[Ω·cm])
[0215] ·Barium sulfate 680 parts
[0216] (Average particle size: 0.60 [μm])
[0217] ·Toluene 6000 parts
[0218] Dispersant (phosphate surfactant) 7 parts
[0219] Defoaming agent (silicone, solid content concentration: 1%) 550 parts
[0220] Except that the resin liquid 1 was changed to the resin liquid 11 , the other steps were the same as those in Example 1 to obtain the carrier 11 .
[0221] (Example 12)
[0222] <Resin liquid 12>
[0223] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0224] Silicone resin solution (solid content: 40%) 2000 parts
[0225] ·Aminosilane (solid content: 100%) 35 parts
[0226] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0227] (Powder resistivity: 40[Ω·cm])
[0228] ·Barium sulfate 680 parts
[0229] (Average particle size: 0.60 [μm])
[0230] ·Toluene 6000 parts
[0231] Dispersant (phosphate surfactant) 190 parts
[0232] Defoaming agent (silicone, solid content concentration: 1%) 550 parts
[0233] Except that the resin liquid 1 was changed to the resin liquid 12 , the other steps were the same as those in Example 1 to obtain the carrier 12 .
[0234] (Example 13)
[0235] <Resin liquid 13>
[0236] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0237] Silicone resin solution (solid content: 40%) 2000 parts
[0238] ·Aminosilane (solid content: 100%) 35 parts
[0239] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0240] (Powder resistivity: 40[Ω·cm])
[0241] ·Barium sulfate 680 parts
[0242] (Average particle size: 0.60 [μm])
[0243] ·Toluene 6000 parts
[0244] Dispersant (phosphate surfactant) 37 parts
[0245] · Defoaming agent (silicone, solid content concentration: 1%) 100 parts
[0246] Except that the resin liquid 1 was changed to the resin liquid 13 , the other steps were the same as those in Example 1 to obtain the carrier 13 .
[0247] (Example 14)
[0248] <Resin liquid 14>
[0249] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0250] Silicone resin solution (solid content: 40%) 2000 parts
[0251] ·Aminosilane (solid content: 100%) 35 parts
[0252] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0253] (Powder resistivity: 40[Ω·cm])
[0254] ·Barium sulfate 680 parts
[0255] (Average particle size: 0.60 [μm])
[0256] ·Toluene 6000 parts
[0257] Dispersant (phosphate surfactant) 37 parts
[0258] · Defoaming agent (silicone, solid content concentration: 1%) 1030 parts
[0259] Except that the resin liquid 1 was changed to the resin liquid 14 , the other steps were the same as those in Example 1 to obtain the carrier 14 .
[0260] (Example 15)
[0261] A carrier 15 was obtained in the same manner as in Example 1 except that barium sulfate was replaced with magnesium oxide (average particle size: 0.55 μm).
[0262] (Example 16)
[0263] A carrier 16 was obtained in the same manner as in Example 1 except that barium sulfate was replaced with magnesium hydroxide (average particle size: 0.61 μm).
[0264] (Example 17)
[0265] A carrier 17 was obtained in the same manner as in Example 1 except that barium sulfate was replaced with hydrotalcite (average particle size: 0.58 μm).
[0266] (Example 18)
[0267] A carrier 18 was obtained in the same manner as in Example 1 except that the aluminum oxide surface-treated with tungsten oxide-doped tin oxide (WTO) was replaced with aluminum oxide surface-treated with indium oxide-doped tin oxide (ITO) (powder resistivity 20·Ωcm).
[0268] (Example 19)
[0269] In addition to changing the aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO) to aluminum oxide surface treated with phosphorus oxide-doped tin oxide (PTO) (powder resistivity 210
[0270] Ω·cm), the rest was the same as in Example 1 to obtain a carrier 19.
[0271] (Comparative Example 1)
[0272] <Resin liquid 20>
[0273] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0274] Silicone resin solution (solid content: 40%) 2000 parts
[0275] ·Aminosilane (solid content: 100%) 35 parts
[0276] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0277] (Powder resistivity: 40[Ω·cm])
[0278] ·Barium sulfate 680 parts
[0279] (Average particle size: 0.60 [μm])
[0280] ·Toluene 6000 parts
[0281] Dispersant (phosphate surfactant) 0 parts
[0282] · Defoaming agent (silicone, solid content concentration: 1%) 0 parts
[0283] The carrier 20 was obtained in the same manner as in Example 1 except that the resin liquid 1 was changed to the resin liquid 20 .
[0284] (Comparative Example 2)
[0285] <Resin liquid 21>
[0286] Acrylic resin solution (solid content concentration: 20%) 200 parts
[0287] Silicone resin solution (solid content: 40%) 2000 parts
[0288] ·Aminosilane (solid content: 100%) 35 parts
[0289] · 1160 parts of aluminum oxide surface treated with tungsten oxide-doped tin oxide (WTO)
[0290] (Powder resistivity: 40[Ω·cm])
[0291] ·Barium sulfate 680 parts
[0292] (Average particle size: 0.60 [μm])
[0293] ·Toluene 6000 parts
[0294] Dispersant (phosphate surfactant) 37 parts
[0295] · Defoaming agent (silicone, solid content concentration: 1%) 0 parts
[0296] The carrier 21 was obtained in the same manner as in Example 1 except that the resin liquid 1 was changed to the resin liquid 21 .
[0297] The properties of the obtained carrier are shown in Table 1. The "dispersant addition amount (parts)" described below means "the addition amount (parts) relative to 100 parts by mass of the total amount of charged fine particles A and conductive fine particles B", and the "defoamer addition amount (parts)" means "the defoamer solid component addition amount (parts) relative to 100 parts by mass of the total amount of resin solid components (acrylic resin solution solid components, silicone resin solution solid components, aminosilane, charged fine particles A, conductive fine particles B, dispersant)".
[0298] Table 1
[0299]
[0300] <Toner Production Example>
[0301] -Synthesis of polyester resin A-
[0302] In a reaction tank equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 65 parts of bisphenol A ethylene oxide 2 mole adduct, 86 parts of bisphenol A propylene oxide 3 mole adduct, 274 parts of terephthalic acid, and 2 parts of dibutyltin oxide were charged and reacted at 230° C. for 15 hours under normal pressure. Then, the reaction was carried out for 6 hours under a reduced pressure of 5-10 mmHg to synthesize a polyester resin A. The obtained polyester resin A had a number average molecular weight Mn of 2,300, a weight average molecular weight Mw of 8,000, a glass transition temperature Tg of 58° C., an acid value of 25 mgKOH / g, and a hydroxyl value of 35 mgKOH / g.
[0303] -Synthetic prepolymers (polymers that react with active hydrogen-containing compounds)-
[0304] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 682 parts of bisphenol A ethylene oxide 2 molar adduct, 81 parts of bisphenol A propylene oxide 2 molar adduct, 283 parts of terephthalic acid, 22 parts of trimellitic anhydride, and 2 parts of dibutyltin oxide were added, and reacted at 230° C. for 8 hours under normal pressure. Then, the reaction was carried out for 5 hours under a reduced pressure of 10-15 mmHg to synthesize an intermediate polyester.
[0305] The obtained intermediate polyester had a number average molecular weight Mn of 2,100, a weight average molecular weight Mw of 9,600, a glass transition temperature Tg of 55° C., an acid value of 0.5, and a hydroxyl value of 49.
[0306] Next, 411 parts of the intermediate polyester, 89 parts of isophorone diisocyanate, and 500 parts of ethyl acetate were added to a reaction container equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, and reacted at 100° C. for 5 hours to synthesize a prepolymer (a polymer capable of reacting with the active hydrogen-containing compound).
[0307] The free isocyanate content of the obtained prepolymer was 1.60% by mass, and the solid content concentration of the prepolymer (after being left to stand at 150° C. for 45 minutes) was 50% by mass.
[0308] -Synthesis of Ketimine (the Active Hydrogen-Containing Compound)-
[0309] In a reaction container equipped with a stirring rod and a thermometer, 30 parts of isophorone diamine and 70 parts of methyl ethyl ketone were added and reacted at 50° C. for 5 hours to synthesize a ketimine compound (the active hydrogen-containing compound). The amine value of the obtained ketimine compound (the active hydrogen-containing compound) was 423.
[0310] -Preparation of Masterbatch-
[0311] 1000 parts of water, 540 parts of carbon black Printex 35 (manufactured by Degussa) having a DBP oil absorption of 42 mL / 100 g and a pH of 9.5, and 1200 parts of polyester resin A were mixed using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.). The obtained mixture was then kneaded at 150° C. for 30 minutes using a two-roll kneader, rolled and cooled, and pulverized using a granulator (manufactured by Hosokawa Micron) to prepare a masterbatch.
[0312] -Preparation of water-based media-
[0313] 306 parts of ion exchange water, 265 parts of a 10 mass % suspension of tricalcium phosphate, and 1.0 part of sodium dodecylbenzenesulfonate were mixed and stirred to uniformly dissolve them, thereby preparing an aqueous medium.
[0314] -Measurement of critical micelle concentration-
[0315] The critical micelle concentration of the surfactant is measured by the following method: Use a surface tension meter Sigma (manufactured by KSV Instruments) and analyze it using the analysis program in the Sigma system. Add the surfactant little by little at 0.01% relative to the water-based medium, stir it, and measure the surface tension after standing. From the obtained surface tension curve, calculate the surfactant concentration at which the surface tension does not decrease even if the surfactant is dropped, as the critical micelle concentration. The critical micelle concentration of sodium dodecylbenzene sulfonate relative to the water-based medium is measured using a surface tension meter Sigma, and the mass relative to the water-based medium is 0.05%.
[0316] -Preparation of toner material liquid-
[0317] 70 parts of polyester resin A, 10 parts of prepolymer, and 100 parts of ethyl acetate were added to a beaker and stirred to dissolve. 5 parts of paraffin wax (HNP-9, melting point 75°C, manufactured by Nippon Seira Co., Ltd.), 2 parts of MEK-ST (manufactured by Nissan Chemical Industries, Ltd.), and 10 parts of masterbatch were added as a release agent, and the above dispersion operation was performed three times using an ultravisco bead mill (manufactured by AIMEX Co., Ltd.) at a liquid feeding speed of 1 kg / hour and a grinding disc peripheral speed of 6 m / second, with 0.5 mm particle size zirconium oxide beads filled at 80 volume %, and then 2.7 parts of the ketimine were added to dissolve to prepare a toner material liquid.
[0318] -Preparation of emulsions and dispersions-
[0319] 150 parts of the aqueous medium was placed in a container and stirred at 12,000 rpm using a TK homomixer (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.), and 100 parts of the toner material liquid was added thereto and mixed for 10 minutes to prepare an emulsified or dispersed liquid (emulsified slurry).
[0320] -Removal of organic solvents-
[0321] 100 parts of the emulsified slurry was added to a flask equipped with a stirrer and a thermometer, and the solvent was removed at 30° C. for 12 hours while stirring at a peripheral speed of 20 m / min to prepare a dispersed slurry.
[0322] - Cleaning -
[0323] After filtering 100 parts of the dispersed slurry under reduced pressure, add 100 parts of ion exchange water to the filter cake, mix with a TK-type homogenizer (at a speed of 12,000 rpm for 10 minutes) and filter. Add 300 parts of ion exchange water to the obtained filter cake, mix with a TK-type homogenizer (at a speed of 12,000 rpm for 10 minutes) and filter, and perform this operation twice. Add 20 parts of a 10 mass% sodium hydroxide aqueous solution to the obtained filter cake, mix with a TK-type homogenizer (at a speed of 12,000 rpm for 30 minutes) and filter under reduced pressure. Add 300 parts of ion exchange water to the obtained filter cake, mix with a TK-type homogenizer (at a speed of 12,000 rpm for 10 minutes) and filter. Add 300 parts of ion exchange water to the obtained filter cake, mix with a TK-type homogenizer (at a speed of 12,000 rpm for 10 minutes) and filter, and perform this operation twice. To the obtained filter cake, 20 parts of 10% by mass hydrochloric acid was further added, mixed with a TK type homogenizer (rotation speed 12,000 rpm, 10 minutes), and then filtered.
[0324] -Adjust the amount of surfactant-
[0325] 300 parts of ion exchange water was added to the filter cake obtained by the above washing, and the mixture was mixed with a TK type homogenizer (rotation speed 12,000 rpm, 10 minutes). The conductivity of the toner dispersion was measured, and the surfactant concentration of the toner dispersion was calculated based on the calibration line of the surfactant concentration prepared in advance. Based on this value, ion exchange water was added to make the surfactant concentration reach the target surfactant concentration of 0.05%, and a toner dispersion was obtained.
[0326] -Surface treatment process-
[0327] The toner dispersion adjusted to a predetermined surfactant concentration was heated in a water bath at a heating temperature T1 = 55° C. for 10 hours while mixing at 5,000 rpm using a TK-type homogenizer. Thereafter, the toner dispersion was cooled to 25° C. and filtered. Next, 300 parts of ion exchange water was added to the obtained filter cake, mixed using a TK-type homogenizer (rotation speed 12,000 rpm, 10 minutes), and then filtered.
[0328] -dry-
[0329] The final filter cake was dried at 45° C. for 48 hours using an air circulation dryer and sieved using a 75 μm mesh to obtain toner mother particles 1.
[0330] -External Additive Processing-
[0331] Furthermore, 3.0 parts of hydrophobic silica having an average particle size of 100 nm, 1.0 part of titanium oxide having an average particle size of 20 nm, and 1.5 parts of hydrophobic silica fine powder having an average particle size of 15 nm were mixed with 100 parts of toner base particles 1 in a Henschel mixer to obtain "Toner 1".
[0332] <Preparation of Developer>
[0333] The "Carrier 1" to "Carrier 21" (93 parts) obtained in the Examples and Comparative Examples and "Toner 1" (7 parts) were mixed and stirred at 81 rpm for 3 minutes using a turbine mixer to prepare "Developer 1" to "Developer 21" for evaluation. Furthermore, replenishment developers for these developers were prepared using the carrier and the toner so that the toner concentration was 95%.
[0334] <Evaluation of Developer Characteristics>
[0335] The obtained "Developer 1" to "Developer 21" were evaluated in the following manner.
[0336] As an evaluation of carrier adhesion at the initial printing stage where the coating resin film is not worn, the following evaluation of initial solid image carrier adhesion of developer characteristic evaluation 1 was performed, as an evaluation of resistance reduction during long-term printing, the following evaluation of solid image carrier adhesion over a long period of time was performed, and as an evaluation of charging properties imparted to the toner, the following evaluation of initial charging properties, charging stability over a long period of time, and toner scattering were performed in developer characteristic evaluation 3. In addition, the digital full-color multifunction machine used for evaluation (Ricoh Co., Ltd., Pro C9100) is a color mass-production printer, and the following developer characteristic evaluations 2 and 3 were used to evaluate the continuous paper feed of the print density at a low image area ratio even in a high-speed machine using a low-temperature fixing toner.
[0337] <Developer Characteristics Evaluation 1>
[0338] The obtained developer was used and installed in a commercially available digital full-color multifunction machine (ProC9100 manufactured by Ricoh Corporation) to perform image evaluation.
[0339] (Solid image carrier attachment)
[0340] The machine was operated in a laboratory environment (25° C., 60% environment) using the developers 1 to 21 of the examples and comparative examples.
[0341] The image was formed under the given development conditions (charging potential (Vd): -600V, potential after exposure to the image portion (solid image original): -100V, development bias: DC-500V). During the formation of the solid image, the image was interrupted by turning off the power supply, etc., and the number of carriers attached to the photosensitive body after transfer was counted and evaluated. The evaluation area was set to an area of 10mm×100mm on the photosensitive body.
[0342] ◎The number of carriers attached is 0
[0343] ○The number of carriers attached is 1 to 3
[0344] △The number of carriers attached is 4 to 10
[0345] × The number of carriers attached is 11 or more.
[0346] ◎, ○, △ are set as qualified, and × is set as unqualified.
[0347] <Developer Characteristics Evaluation 2>
[0348] The obtained developer was installed in a commercially available digital full-color multifunction machine (Ricoh Co., Ltd., ProC9100) to perform image evaluation. Specifically, the machine was operated at an image area ratio of 0.5% for 1 million sheets in a laboratory environment (25°C, 60% environment) using the developers 1 to 21 of the examples and comparative examples and their replenishing developers, and the solid image carrier adhesion after the operation was evaluated. The evaluation was performed in the same manner as above except that the evaluation was performed after the 1 million sheet operation.
[0349] <Developer Characteristics Evaluation 3>
[0350] (Initial charge)
[0351] Relative to the initial carrier 93% by mass, the toner is mixed at a ratio of 7% by mass, and the measurement is performed using BLOW OFF TB-200 (manufactured by Toshiba Chemical Co., Ltd.). At this time, the carrier and the toner are mixed, and the charge amount at 15 seconds after the start of mixing is set as Q1, and the charge amount at 600 seconds after the start of mixing is set as Q2. The initial chargeability is defined as the absolute value of (Q1-Q2) / (Q1)×100. The evaluation criteria are as follows:
[0352] 15 and above: ◎ (very good)
[0353] 10 or more to less than 15: ○ (good)
[0354] 5 or more to less than 10: △ (usable)
[0355] 0 or more to less than 5: × (difference)
[0356] (Long-term charge stability)
[0357] In Ricoh Pro C9100 (Ricoh digital color copier / printer), the developers 1 to 21 of Examples and Comparative Examples and their replenishing developers were used to run 1,000,000 sheets at an image area ratio of 40%, and then the carrier was evaluated.
[0358] First, carriers 1 to 21 and toner 1 were mixed at a mass ratio of 93:7 and frictionally charged to obtain a sample, and the initial carrier charge (Q1) was measured using BLOW OFF TB-200 (manufactured by Toshiba Chemical Co., Ltd.). The carrier charge (Q2) after running 1 million sheets was measured in the same manner as above, except that the carriers from which the toners of each color were removed from the developer after running were used using a BLOW OFF device. The rate of change of charge was defined as the absolute value of (Q1-Q2) / (Q1)×100. The evaluation criteria are as follows:
[0359] 0 or more to less than 5: ◎ (very good)
[0360] 5 or more to less than 10: ○ (good)
[0361] 10 or more to less than 20: △ (usable)
[0362] 20 or more: × (poor)
[0363] (Toner scattering)
[0364] In Ricoh Pro C9100 (Ricoh digital color copier / printer), developers 1 to 21 of the examples and comparative examples and their replenishing developers were used to run 1 million sheets at an image area rate of 40%, and the amount of toner accumulated in the lower part of the developer carrier was sucked and recovered to measure the toner quality. The evaluation criteria are as follows:
[0365] 0mg or more to less than 50mg: ◎ (very good)
[0366] 50 mg or more to less than 100 mg: ○ (good)
[0367] 100mg or more to less than 250mg: △ (can be used)
[0368] 250 mg or more: × (bad)
[0369] Table 2 shows the results of the image evaluation.
[0370] Table 2
[0371]
[0372] The embodiments of the present invention have been described above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the technical concept of the present invention, and they all belong to the protection scope of the present invention.
Claims
1. An electrophotographic imaging carrier, comprising a core particle and a resin layer covering the core particle, characterized in that: The resin layer contains charged particles A and conductive particles B, and the resin layer contains a dispersant and a defoaming agent, wherein the dispersant is a phosphate surfactant and the defoaming agent is a silicone defoaming agent, the amount of the dispersant added is greater than 0.5 parts by mass and less than 10.0 parts by mass relative to 100 parts by mass of the total amount of the charged particles A and the conductive particles B, and the solid content of the defoaming agent added is greater than 0.05 parts by mass and less than 0.35 parts by mass relative to 100 parts by mass of the resin layer.
2. The electrophotographic imaging carrier according to claim 1, characterized in that: The charged fine particles A are at least one inorganic fine particle selected from the group consisting of barium sulfate, magnesium oxide, magnesium hydroxide, and hydrotalcite.
3. The electrophotographic imaging carrier according to any one of claims 1 to 2, characterized in that: The conductive particles B are particles of tin oxide doped with any one of tungsten, indium, phosphorus, or any one of the oxides thereof, or particles in which the doped tin oxide is disposed on the surface of a substrate.
4. The electrophotographic imaging carrier according to claim 3, characterized in that: The conductive fine particles B are aluminum oxide fine particles in which tin oxide doped with tungsten or an oxide thereof is provided on the surface of a substrate.
5. The electrophotographic imaging carrier according to claim 4, characterized in that: The charged particles A are barium sulfate.
6. An electrophotographic imaging carrier, comprising a core particle and a resin layer covering the core particle, characterized in that: The resin layer includes charged fine particles A and conductive fine particles B, and contains phosphate ester and silicone oil.
7. A developer for electrophotographic imaging, characterized in that: Use of the electrophotographic image forming carrier according to any one of claims 1 to 6.
8. An electrophotographic imaging method, characterized in that: include: A process of forming an electrostatic latent image on an electrostatic latent image carrier; A step of developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer according to claim 7 to form a toner image; a step of transferring the toner image formed on the electrostatic latent image carrier to a recording medium; as well as A step of fixing the toner image transferred to the recording medium.
9. An electronic photographic imaging device, characterized in that: include: Electrostatic latent image carrier; A charging mechanism for charging the electrostatic latent image carrier; an exposure mechanism for forming an electrostatic latent image on the electrostatic latent image carrier; A developing means for developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer described in claim 7 to form a toner image; A transfer mechanism for transferring the toner image formed on the electrostatic latent image carrier to a recording medium; as well as A fixing mechanism fixes the toner image transferred to the recording medium.
10. A processing cartridge, characterized in that: include: Electrostatic latent image carrier; A charging component for charging the surface of the electrostatic latent image carrier; a developing member for developing the electrostatic latent image formed on the electrostatic latent image carrier using the developer according to claim 7; as well as A cleaning member is provided for cleaning the electrostatic latent image carrier.
Citation Information
Patent Citations
Electrophotographic carrier, electrophotographic two-component developer, and image forming method
JP2010230836A
Electrostatic latent image developing carrier, method for manufacturing the carrier, developer, container containing developer, image forming method, and process cartridge
JP2011209678A
Carrier and developer
JP2016212254A
Carrier for electrostatic latent image developer, two-component developer using the same, developer for replenishment, toner storage unit, and image forming apparatus
JP2017167387A
Developing apparatus, image forming apparatus, image forming method
JP2018155970A